Dusuqing granules (DSQ) suppress inflammation in Klebsiella pneumonia rat via NF-κB/MAPK signaling - Xue Mei; Hao-Xun Wang; Jian-Sheng Li; Xiao-Hui Liu; Xiao-Fan Lu; Ya Li; Wei-Yu Zhang; Yan-Ge Tian (BMC, 2017)
Abstract Background Dusuqing granules (DSQ) have been used in the treatment of bacterial pneumonia clinically, with remarkable benefits. This study was initiated to explore the effects of DSQ on pulmonary inflammation by regulating nuclear factor (NF)-κB/mitogen-activated protein kinase (MAPK) signaling in bacterial pneumonia rats. Methods Rat model was duplicated with Klebsiella pneumonia by a one-time intratracheal injection. Rats were randomized into control, model, DSQ and levofloxacin (LVX) groups. After administrated with appropriate medicines for 7 days, lung tissues were harvested and prepared for pathological analysis, and interleukin (IL)-1, IL-6, monocyte chemotactic protein (MCP)-1and macrophage inflammatory protein (MIP)-2 detections. NF-κB mRNA was measured by real-time qPCR, and the phosphorylation and total proteins of P38MAPK, JNK46/54, ERK42/44 were determined by Western blotting. Results Marked pathological impairments were observed in model rats, whereas were improved in DSQ group. The cytokines levels, NF-κB mRNA expression and the phosphorylation of P38MAPK, JNK46/54 and ERK42/44 proteins were significantly higher in model group, and were significantly depressed in DSQ group. Conclusion The protective effects of DSQ on Klebsiella pneumonia might be attributed to its inactivative effects of NF-κB/ MAPK pathway.